Pengolahan Limbah Elektronik (E-Waste) Mix Resin Sebagai Embrio Usaha Berbasis Seni Estetika - Tri Puspita Sari; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Andi Irma Eka Rahayu; Andi Sitti Noer Azizah (Unri Conference Series: Community Engagement, 2021)
This Community Service is a Student Creativity Program carried out by the partners of the Karang Taruna Group, Batulappa Village, Patimpeng District, Bone Regency. This activity aims to solve problems regarding E-Waste that occur due to continuous accumulation. E-Waste buildup usually occurs due to minor damage or has entered the end of use. E-Waste is one of the wastes made from hazardous materials, so it includes hazardous and toxic materials (B3) whose concentration will affect health and pollute the environment if it accumulates. E-Waste Processing, a very crucial impact is that generally the owner of the electronic service only burns the generated electronic waste. However, this can pollute the air and environmental ecosystems, so other efforts are needed in overcoming and reducing electronic waste for education to the Karang Taruna Group in Batulappa Village. E-Waste mix resin can be used as a means to channel the creativity of the Karang Taruan Group in Batulappa Village as a partner by processing the components that exist in E-Waste. The work produced can be commercialized with a high selling value to help improve the partner's economy as a provision for future skills for entrepreneurship.